Composición, distribución y abundancia de larvas de moluscos gastrópodos en el sur de Quintana Roo, México y norte de Belice - Oliva Rivera, J (2000)
To know the composition, abundance and distribution of gastropod larvae, monthly samplings were carried out in the south of Quintana Roo, Mexico and north of Belize, from April to December, 1996. Collections were made in six sites at Chinchorro Bank, four in the South Coast and six at Hol-Chan, Belize, between the 10 and 20 hrs. At each station 2.5 m3 of seawater were pumped through a 202 μm mesh; 27 species were identified. The most abundant species were: South Coast, Rissoina sp. 1., Limacina sp. 1 and Natica sp. 1, Chinchorro Bank, Limacina sp. 1, Creseis acicula, Cerithiopsis hero and Rissoina sp.1 and Hol-Chan, Limacina sp.2, Alaba incerta and Rissoina sp.1. The highest abundance was in rainy season. Apparently the presence of winds, coastal currents and food availability, control the distribution and abundance of larvae.